PENGARUH PELAYANAN FISKUS DAN PENGETAHUAN PERPAJAKAN TERHADAP KESADARAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA SUKOMANUNGGAL SURABAYA - Krisnawati (Soetomo Accounting Review, 2024)
This study aims to examine and analyze the effect of taxation services and tax knowledge on taxpayer awareness simultaneously and partially. The population in this study is an individual taxpayer who is registered at KPP Pratama Sukamanunggal Surabaya. The sample taken is 50 respondents using incidental sampling method. Data analysis used multiple linear regression analysis with SPSS 21 tools. Based on the results of hypothesis testing, the research variables consist of: (1) Fiscal Service and Tax Knowledge together (simultaneously) have a significant effect on taxpayer awareness. (2) Fiscal service has a significant effect on taxpayer awareness, as seen from the significantly higher value. smaller than 0.05, this means that if the tax service service is getting better, it will increase taxpayer awareness. (3) Knowledge of taxation has a significant effect on taxpayer satisfaction, it can be seen from the value significantly less than 0.05, this means that if the knowledge of taxation is getting better, it will increase taxpayer awareness.